THE EFFECT OF FLIPPED CLASSROOM WITH CONCEPT MAPS ON THE LEARNING OUTCOMES OF THIRD-GRADE KMI STUDENTS IN FIQH SUBJECT AT PONDOK MODERN DARUSSALAM GONTOR, CAMPUS IV KALIGUNG-BANYUWANGI - Naufal Hilmi Dzaky, Muhammad; Musyarofah, Atiqatul; Al Muftiyah, Al Muftiyah (International Conference on Humanity Education and Society (ICHES), 2025)
This study aims to analyze the effect of the Flipped Classroom learning model integrated with concept maps on the learning outcomes of third-grade KMI students in the Fiqh subject at Pondok Modern Darussalam Gontor, Campus 4 Banyuwangi. Thisresearch employs a quantitative quasi-experimental approach with a post-test only one-group design. The sample was selected using a cluster sampling technique, consisting of students from classes III-D and III-B. Data were collected through observation, tests, and documentation. The data were analyzed using t-test and effect size techniques. The validity of the data was ensured through validity and reliability testing, as well as prerequisite tests including homogeneity and normality tests. The results showed that the t-test value (t = 2.854) was greater than the critical t-value (t = 2.021), with a significance value (sig. 2-tailed) of 0.014 < 0.05. This indicates that the hypothesis stating there is a significant effect of using the Flipped Classroom model with concept maps on students' learning outcomes is accepted, while the null hypothesis is rejected. Furthermore, the effect size (Cohen’s d) was calculated using the formula: Cohen’s d = (Mean 1 – Mean 2) / Pooled Standard Deviation = (14.45 17.30)/3.591 = 0.794. This result indicates a moderately large effect.